PEMANFAATAN POTENSI ALAM MELALUI PELATIHAN PEMBUATAN SABUN BAGI KELOMPOK PEREMPUAN DI DESA DANGIANG, KECAMATAN KAYANGAN, KABUPATEN LOMBOK UTARA - Rahmawati, Diah; Alpiana, Alpiana; Lestanata, Yudhi; Muslimin, Muslimin; Hafsah, Hafsah; Adiansyah, Joni Safaat (Universitas Muhammadiyah Mataram, 2021)
Abstrak: Desa Dangiang memiliki sumberdaya kelapa yang melimpah tetapi harga jual kelapa yang sangat rendah. Masyarakat terbiasa membuat minyak kelapa untuk kebutuhan sehari-hari. Pelatihan pembuatan sabun berbahan minyak kelapa dimaksudkan untuk meningkatkan nilai jual kelapa sehingga dapat menambah penghasilan masyarakat. Metode pembuatan sabun yang dipraktikkan adalah metode cold proses dengan dua pilihan resep sabun, yakni 100% minyak kelapa dan campuran minyak kelapa, minyak kelapa sawit, dan minyak zaitun. Serbuk kelor ditambahkan karena selain berkhasiat sebagai antioksidan juga sebagai pewarna alami. Hasil pelatihan berupa sabun batang. Tanggapan masyarakat setelah menggunakan sabun buatan tersebut sangat positif, karena nyaman dipakai dan disukai oleh masyarakat. Sabun tersebut juga tidak mengandung bahan berbahaya seperti dietanolamine (DEA), Sodium Lauryl Sulfate (SLS), dan Triclosan. Ketertarikan masyarakat terhadap sabun tersebut menumbuhkan minat masyarakat untuk dapat memproduksi sabun sendiri dan berharap sabun tersebut dapat di perdagangkan sehingga dapat menambah pendapatan masyarakat. Abstract: Dangiang Village has abundant coconut resources, but the selling price is meager. People are used to making coconut oil for their daily needs. The training in making soap made from coconut oil is intended to increase the villager’s income. The method of making soap used is the cold process method with two choices of soap recipes, namely 100% coconut oil and a mixture of coconut oil, palm oil, and olive oil. Moringa powder is added because besides being an antioxidant, it is also a natural dye. The resulting soap is a bar soap that is comfortable to use and is liked by the community. The soap also does not contain harmful ingredients such as diethanolamine (DEA), Sodium Lauryl Sulfate (SLS), and Triclosan. The villagers are interested in making the soap and hope that the soap can be traded so that it can increase people’s income.Dangiang Village has abundant coconut resources, but the selling price is meager. People are used to making coconut oil for their daily needs. The training in making soap made from coconut oil is intended to increase the villager’s income. The method of making soap used is the cold process method with two choices of soap recipes, namely 100% coconut oil and a mixture of coconut oil, palm oil, and olive oil. Moringa powder is added because besides being an antioxidant, it is also a natural dye. The resulting soap is a bar soap that is comfortable to use and is liked by the community. The soap also does not contain harmful ingredients such as diethanolamine (DEA), Sodium Lauryl Sulfate (SLS), and Triclosan. The villagers are interested in making the soap and hope that the soap can be traded so that it can increase people’s income.